2008
DOI: 10.1161/hypertensionaha.107.105205
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in Blood Pressure Control and Cardiovascular Risk Factors in Americans With Diagnosed Hypertension

Abstract: Abstract-Hypertension is an important risk factor for cardiovascular disease, which is the leading cause of death in women. We, therefore, analyzed gender-specific trends in the control of blood pressure and prevalence of 5 other cardiovascular risk factors (central obesity, elevated total cholesterol, low high-density lipoprotein cholesterol, hyperglycemia, and smoking) among adults with diagnosed hypertension in the United States. We included 3475 participants aged Ն18 years with diagnosed hypertension in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
154
4
14

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(194 citation statements)
references
References 33 publications
22
154
4
14
Order By: Relevance
“…The NHANES 1999-2004 showed that 50.8% of men and 55.9% of women had uncontrolled hypertension adjusted for age. 5 Rates of uncontrolled hypertension were positively related with age with only 29% of hypertensive women aged 70-79 years having clinic BP o140/90 mm Hg compared with 41 and 37% of those 50-59 and 60-69 years of age, respectively (Figure 2). 26 An increased prevalence of concomitant CV factors, including central obesity, elevated total cholesterol and low high-density lipoprotein cholesterol levels are likely to contribute to poor BP control in elderly women.…”
Section: Risk In Womenmentioning
confidence: 97%
See 3 more Smart Citations
“…The NHANES 1999-2004 showed that 50.8% of men and 55.9% of women had uncontrolled hypertension adjusted for age. 5 Rates of uncontrolled hypertension were positively related with age with only 29% of hypertensive women aged 70-79 years having clinic BP o140/90 mm Hg compared with 41 and 37% of those 50-59 and 60-69 years of age, respectively (Figure 2). 26 An increased prevalence of concomitant CV factors, including central obesity, elevated total cholesterol and low high-density lipoprotein cholesterol levels are likely to contribute to poor BP control in elderly women.…”
Section: Risk In Womenmentioning
confidence: 97%
“…1 In the data from the NHANES 1999-2004 women were at significantly higher CV risk compared with men, with 53% of women and 41% of men with X3 of the six risk factors studied. 5 However, hypertension control in women remains poor, especially among elderly women. The NHANES 1999-2004 showed that 50.8% of men and 55.9% of women had uncontrolled hypertension adjusted for age.…”
Section: Risk In Womenmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent survey of patients with diagnosed hypertension, central obesity was significantly more prevalent in women than men (79 vs 64%), as were elevated total cholesterol (61 vs 48%) and low HDL cholesterol (40 vs 36%). 26 Furthermore, significantly more women than men had three or more cardiovascular risk factors (53 vs …”
Section: Discussionmentioning
confidence: 99%